2021
DOI: 10.1109/access.2021.3055342
|View full text |Cite
|
Sign up to set email alerts
|

Tactile Paving Detection by Dynamic Thresholding Based on HSV Space Analysis for Developing a Walking Support System

Abstract: In this research, we present a system that enables independent walking in individuals with visual impairment by recognizing tactile paving. The system warns the user about dangers posed by deviations from the walking path or possible collisions. Therefore, the tactile paving itself and obstacles on it must be detected. This paper discusses problems related to detecting tactile paving. To address these problems, a new camera-based method is introduced, which detects tactile paving automatically. The method reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 26 publications
(27 reference statements)
0
7
0
1
Order By: Relevance
“…However, we could apply some of those works to achieve only straight motions in this study. Furthermore, many studies can be found in the literature for obstacle detection and avoidance [5,33,40,41,45,[49][50][51][52]. However, in this study, the obstacle avoidance was done by keeping a constant distant from the obstacle, as shown in Figure 8.…”
Section: Discussion Regarding Conventional Methodsmentioning
confidence: 99%
“…However, we could apply some of those works to achieve only straight motions in this study. Furthermore, many studies can be found in the literature for obstacle detection and avoidance [5,33,40,41,45,[49][50][51][52]. However, in this study, the obstacle avoidance was done by keeping a constant distant from the obstacle, as shown in Figure 8.…”
Section: Discussion Regarding Conventional Methodsmentioning
confidence: 99%
“…It has been beneficial in several real-life applications including but not limited to the following. First, the Hough transform is a handy tool for detecting tactile pavement, assisting visually impaired individuals to walk in public places [15]. Second, it is the primary method used in precision agriculture to detect crop rows and direct UAVs in selectively spraying agrochemicals in the field [16].…”
Section: A Line-based Methodsmentioning
confidence: 99%
“…Many techniques [ 50 , 51 , 52 ] in the recent literature do not analyze the chromaticity information to threshold color images, since they incorporate RGB-channel-based thresholding. While some [ 10 , 53 , 54 ] do apply HSV or L*A*B* color space analysis to thresholding problems, they do not automatically determine the threshold limits based on the unique characteristics of the image. Our proposed method determines the chromaticity of the background or foreground pixels using the hue and saturation histograms and computes the optimal color threshold by considering the changes in histogram gradient and histogram cumulative area.…”
Section: Related Workmentioning
confidence: 99%